Answer:
See Explanation
Step-by-step explanation:
<em>The question is incomplete as the function is not given. However, the following explanation will guide you.</em>
<em></em>
The average rate of change is calculated using;
![A = \frac{f(b) - f(a)}{b - a}](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7Bf%28b%29%20-%20f%28a%29%7D%7Bb%20-%20a%7D)
Where
![(a,b) = (-1,5)](https://tex.z-dn.net/?f=%28a%2Cb%29%20%3D%20%28-1%2C5%29)
Take for instance;
The function is:
![f(x) = 2x](https://tex.z-dn.net/?f=f%28x%29%20%3D%202x)
We have to solve for f(-1) and f(5);
i.e.
![f(-1) = 2 * -1 -2](https://tex.z-dn.net/?f=f%28-1%29%20%3D%202%20%2A%20-1%20%20-2)
![f(5) = 2 * 5 = 10](https://tex.z-dn.net/?f=f%285%29%20%3D%202%20%2A%205%20%3D%2010)
Substitute -1 for a and 5 for b
![A = \frac{f(b) - f(a)}{b - a}](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7Bf%28b%29%20-%20f%28a%29%7D%7Bb%20-%20a%7D)
![A = \frac{f(5) - f(-1)}{5 - (-1)}](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7Bf%285%29%20-%20f%28-1%29%7D%7B5%20-%20%28-1%29%7D)
![A = \frac{f(5) - f(-1)}{5 +1)}](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7Bf%285%29%20-%20f%28-1%29%7D%7B5%20%2B1%29%7D)
![A = \frac{f(5) - f(-1)}{6}](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7Bf%285%29%20-%20f%28-1%29%7D%7B6%7D)
Substitute values for f(5) and f(-1)
![A = \frac{10 - (-2)}{6}](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7B10%20-%20%28-2%29%7D%7B6%7D)
![A = \frac{10 +2}{6}](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7B10%20%2B2%7D%7B6%7D)
![A = \frac{12}{6}](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7B12%7D%7B6%7D)
![A = 2](https://tex.z-dn.net/?f=A%20%3D%202)
<em>Apply this steps in your work</em>
Answer:
False
Step-by-step explanation:
There is not a one in the 2 expression listed
Answer:
umm why not ask the teacher for help they will help you
Step-by-step explanation:
Answer:
135°
Step-by-step explanation:
LI = LM+MI = 35+80
Answer:
62652
Step-by-step explanation:
15553